Circularly Polarized Cylindrical Dielectric Resonator Antenna with Fractal Cross-Slot: Design, Analysis, and Performance Evaluation - Pedada Krishna Rao (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This work focuses on the development and design of a Circularly Polarized Cylindrical Dielectric Resonator Antenna (CDRA) incorporating a Fractal Cross Slot. The antenna is planned for applications requiring enhanced performance in wireless communication systems. The proposed design unites the advantages of circular polarization for reduced signal fading and the unique characteristics brought about by the incorporation of a fractal cross slot. The results in the simulation are showed that it has wonderful impedance bandwidth and radiation efficiency that it is a kind of good performance. But due to the advantages of Fractal-slot-aperture coupled DRA antennas in the wireless application, it is designed further. In this innovative design, a Circularly Polarized (CP) Dielectric Resonator Antenna (DRA) is coupled with a fractal cross-slot, effectively enhancing radiation efficiency. Through meticulous adjustment of the fractal cross-slot dimensions, resonance from both the fractal cross-slot and the dielectric resonator can be merged, leading to a significantly wider Axial Ratio (AR) bandwidth. This novel approach allows for the creation of an antenna meticulously tailored for optimal performance, leveraging the benefits of the fractal cross-slot coupled CP DRA element. The cylindrical dielectric resonator serves as the radiating element, providing a compact and efficient structure. Circular polarization is achieved through careful design considerations, optimizing the orientation and configuration of the dielectric resonator. The use of fractal geometry introduces additional resonances and modifies the radiation characteristics of the antenna. Fractals are employed to enhance the antenna's bandwidth, reduce size, and achieve multi-band capabilities. The resulted patterns are utilized to calculate the antenna's radiation pattern, gain, VSWR, return loss, axial ratio, directivity. Measurements include radiation pattern analysis, and circular polarization verification. The experimental results are compared with simulation predictions, validating the effectiveness of the proposed design. The integration of circular polarization and fractal geometry contributes to improved performance metrics, making the antenna well-suited for modern communication systems requiring compact, high-performance antennas. The findings of this research may advance the state-of-the-art in antenna design and pave the way for practical applications in emerging wireless technologies.